Development of an Islamic Integrated Biology E-Module on Class XI High School Excretory System Material to Empower Students' Critical Thinking Skills - Wijayanti, Erna; Fadlul Hagma, Muhamad Agus; Ruswan, Ruswan (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
This study aims to develop an Islamic integrated biology e-module on the excretory system material for grade XI high school to empower students' critical thinking skills. The product is developed using a 4-D development model (define, design, develop, and disseminate). The instrument used is a questionnaire. The research subjects comprised 30 class XI IPA students from MA Darul Ulum Semarang. Data collection was conducted through interviews, observations, documentation, and questionnaires. The data were analyzed using descriptive analysis and qualitative techniques. The study resulted in the development of valid e-module products, with validity criteria of 75% from material experts, 85% from Islamic integration experts, and 62.5% from media experts. Additionally, the results showed that practical e-modules were utilized with a practicality percentage of 77.94% based on responses from Biology Teachers and 86.66% from students.